Medicines and elderly people: a general practice survey. Issue 6009 (6th March 1976) - Law, R; Chalmers, C
Abstract : All 151 patients of 75 years and over in one practice were visited at home to survey their health and how they managed their medicines. Altogehter 87% were on regular treatment, 34% taking three or four different drugs each day. Most were responsible for their own drugs and managed them well, but many left their drugs in exposed places and were uncertain about how to dispose of unwanted medicines. Overall they were prescribed about three times the number of drugs prescribed for the general population, and women took twice as many drugs regularly as men. Although many drugs were obtained directly from a pharmacist, his advice was rarely sought. Most were labelled, but more explicit instructions about indications for taking the drug would have been helpful, and information about hoarded drugs would have been enhanced by dispensing and expiry dates. Treatment was facilitated when patients brought their drugs to the consultation and careful records were made of repeat prescriptions. As so many patients take three or more different types of drugs each day a container in which a day's supply could be laid out would be useful.